(3GdGfTWI GdghGFjIs - (3YHO GdQMef fYeGJ CMeOs ((3GdGScfOQjIs (3efTCI GdeYGQas, 2000)
(3JGQjN h CgejI GdCfTWI GdghGFjI h GQJHGWgG HGddjGbI GdHOfjI h GdUNI,HTcd NGU h GdOhQ GdPj JdYHg aj GcJSGH GdJcdja GdXjaj ddCLgRI GdMjhjI,h NaV fSHI GdOgf ,h bOe HYV GdHQGeL GdJOQjHjI eUhQI dHYV GdCfTWI GdghGFjI(B.s
Keywords: (3GdQYGjI GdUMjIs